Brands as advocates on social media: understanding the effects and mechanisms of brand activism communication - Zhou, Xuan (Nanyang Technological University, 2025)
Brand activism describes that brands actively join in sociopolitical conversations by taking stances on pressing issues, such as civil rights and geopolitical conflicts. Yet, it remains largely underexplored how the communicative aspects of brand activism influence consumer reactions. Drawing upon the frameworks of congruence theory and the Source–Message–Channel–Receiver (SMCR) model, the thesis seeks to investigate how the congruence among various communication factors influences the persuasion outcomes of brand activism and elucidate the psychological mechanisms underlying the effects. The thesis begins by introducing the phenomenon of brand activism and presenting the theoretical frameworks and research objectives in Chapter One. Chapter Two focuses on the visual-verbal message compatibility and examines the interplay between image color and message framing in the effectiveness of brand activism advertising. The findings from two experiments indicated that brand activism ads featuring BW images (vs. color images), when paired with promotion-framed (vs. prevention-framed) messages, resulted in more positive ad attitudes and greater intentions to purchase the brand. The level of inspiration that consumers perceived upon viewing the ads was identified as an underlying psychological mechanism. Chapter Three shifts the focus to message-platform congruence and introduces a distinct characteristic of social media, namely, the level of politicization. A scale was first developed to measure the politicization level of social media. Besides, an experimental study tested the message–platform congruence effect in terms of politicization in the context of brand activism. The findings showed that on a less politicized platform, delivering a less politicized (vs. more politicized) activism message could lessen perceived intrusiveness, thereby improving attitudes towards the ads and intentions to purchase from the brand. However, on a highly politicized platform, the type of message did not significantly alter consumer responses. A follow-up experiment further pinpointed that the level of issue support acted as a boundary condition of the congruence effect, with a more pronounced effect observed when there was a low (vs. high) level of issue support. Chapter Four explores the dynamics of the emotional landscape in brand activism communication and examines the role congruity between brand gender (masculinity vs. femininity) and emotion expression (anger vs. sadness). The findings from two experiments revealed that anger expression (sadness expression) was perceived to be more congruent with the stereotypical roles of masculine brands (feminine brands). Moreover, stereotype-congruent expressions improved conservatives’ perceived appropriateness and message attitudes more profoundly, while non-stereotypical expressions were more effective at enhancing liberals’ advocacy intentions. Chapter Five summarizes the theoretical and practical implications derived from the findings. This thesis contributes to a more nuanced understanding of the communicative dimensions of brand activism. In practical terms, this thesis offers insights that can guide more effective approaches in strategic communication contexts.